A Brief Review of Probiotic: Action Mechanism, Benefits, and Clinical Application on Human Health - Dewa Ayu Agus Sri Laksemi; I Ketut Tunas; Ni Luh Putu Eka Diarthini (Journal of Global Pharma Technology, 2018)
Probiotics are live microorganisms that are commonly used as food supplementation to provide a positive impact on human health. There was an increasing number of studies concerned with the benefit of probiotics due to the enhance community awareness of health. The primarily role of probiotics are known strengthening the epithelial barrier, increasing attachment to the intestinal mucosa, inhibiting the attachment of pathogenic bacteria, competitive exclusion of pathogenic microorganisms, producing anti-microbial substances and thereby modulating host immunity by initiating specific genes activation in the host intestinal tract system. The benefits of probiotics are not only limited to the gastrointestinal system but the mechanism of action includes other organs such as respiratory, urogenital, endocrine, and immune system. Hence, this review study will focus mainly on three aspects such as benefits, action mechanism, and its clinical application of probiotics on human health.Keywords: Action mechanism, Benefits, Clinical application, Probiotics.